High-strength high-corrosion-resistance ultra-pure austenitic stainless steel and manufacturing method thereof
By adding specific elements to ultra-pure austenitic stainless steel and controlling its content, combined with the low-temperature large deformation forging method, the problem of ultra-pure austenitic stainless steel is solved, and ultra-pure austenitic stainless steel is easily cracked and uneven grains during the forging process, achieving high strength and high corrosion resistance.
Patent Information
- Application Number
- CN202411891555.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
Existing ultrapure austenitic stainless steels are prone to cracks during forging, and their grains are uneven, and their strength and corrosion resistance are insufficient, making it difficult to produce stably in batches.
By adding specific elements to ultrapure austenitic stainless steel and controlling its content, purifying grain boundaries and suppressing grain growth, the forging method of low-temperature and large deformation is adopted, the forging temperature is controlled at 800-950℃, and the total deformation is controlled at 60% to 63%.
The high strength and high corrosion resistance of ultrapure austenitic stainless steel are achieved, making its tensile strength reach more than 520MPa and the yield strength reach more than 230MPa. There is no intergranular corrosion phenomenon after the C corrosion test.
Smart Images

Figure CN119710462A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel manufacturing, and in particular to high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel and a manufacturing method thereof. Background Art
[0002] C25 steel is an ultra-pure austenitic stainless steel with good corrosion resistance, mainly used in the field of spent fuel reprocessing. Due to the ultra-purified smelting process, the carbon content and other impurities are extremely low, ensuring good corrosion resistance, but sacrificing the strength of stainless steel. When used to manufacture spent fuel reprocessing equipment, the selected materials need to have a certain strength to ensure the safe use of the equipment.
[0003] With the traditional forging process, the initial forging temperature is often above 1100℃. At higher forging temperatures, due to the lack of pinning of the precipitated phase at the grain boundary, the grain size of the ultra-pure austenitic steel will rapidly increase, causing a decrease in strength and affecting corrosion resistance. The existing technology is used to produce C25 ultra-pure austenitic stainless steel forgings, and the product quality is relatively random, and it is impossible to carry out stable mass production. The main problems of product quality are manifested in the following two aspects: First, cracks are prone to occur during forging of the steel ingot, which will cause the steel ingot to be scrapped in severe cases; second, the forgings produced fail the performance test, which is mainly manifested in uneven grains, large grain size, and other problems. The strength after solution treatment does not meet the index requirements.
[0004] Therefore, there is an urgent need for an ultra-pure austenitic stainless steel with superior performance, uniform grains and smaller grain size, and no cracks are generated during the manufacturing process. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel and a method for manufacturing the same, so as to obtain high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel without generating cracks during the manufacturing process.
[0006] On the one hand, the present invention provides a high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel, which, in terms of weight percentage, includes C≤0.008%, Si≤0.10%, Mn≤0.50%, P≤0.005%, S≤0.005%, Cr: 24.00%~26.00%, Ni: 20.00%~22.00%, Mo≤0.10%, Al≤0.02%, B<0.003%, Zr≤0.6%, Mg≤0.05%, and the balance is Fe.
[0007] Furthermore, in terms of weight percentage, the austenitic stainless steel includes C: 0.002-0.004%, Si≤0.060%, Mn≤0.30%, P≤0.003%, S≤0.003%, Cr: 24.80%-25.20%, Ni: 21.50%-22%, Mo≤0.80%, Al≤0.15%, B<0.002%, Zr: 0.3%-0.5%, Mg: 0.03%-0.05%, and the balance is Fe.
[0008] Furthermore, the grain size of the ultra-pure austenitic stainless steel is 6.5, and the grain distribution is relatively uniform.
[0009] Furthermore, the ultra-pure austenitic stainless steel has a tensile strength of more than 520 MPa and a yield strength of more than 230 MPa.
[0010] In another aspect, the present invention provides a method for manufacturing high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel, comprising the following steps:
[0011] S1: Ingot preparation;
[0012] S2: Ingot heating;
[0013] S3: multi-fire forging, forging temperature is 800-950℃, final forging temperature is above 600℃, total deformation is 60%~63%;
[0014] S4: Ultra-pure austenitic stainless steel is produced after solution treatment.
[0015] Further, in step S3, the forging times are 4-8 times.
[0016] Furthermore, in step S3, the forging temperature of the first forging is 840°C to 855°C, the final forging temperature is above 600°C, and the deformation amount is 24% to 26%.
[0017] Furthermore, in step S3, the forging temperature of the second fire is 900° C. to 925° C., the final forging temperature is above 600° C., and the deformation amount is 19% to 20.5%.
[0018] Furthermore, in step S3, the forging temperature of the third fire is 790°C to 805°C, the final forging temperature is above 600°C, and the deformation of the central part is controlled to be 19% to 20.5%.
[0019] Further, in step S4, the solution temperature is 950°C-1000°C, and the holding time is 1-2h.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] 1. The present invention can purify the grain boundaries, inhibit the growth of grains, make the grains finer and more uniform by adding elements and controlling the content, which helps to improve the strength and toughness of austenitic stainless steel. At the same time, the fine grains can reduce the segregation of impurities at the grain boundaries and improve the corrosion resistance.
[0022] 2. The ultra-pure austenitic stainless steel of the present invention adopts a low-temperature large deformation forging method, the forging temperature is controlled at 800-950°C, the total deformation is controlled at 60% to 63%, and the forging temperature is much lower than the existing forging temperature (1000-1200°C);
[0023] 3. The optimized element ratio and the low-temperature large deformation forging method can improve the strength and corrosion resistance of the ultra-pure austenitic stainless steel at the same time, so that the tensile strength of the ultra-pure austenitic stainless steel is above 520MPa, the yield strength is above 230MPa, and no intergranular corrosion is found after corrosion in the C corrosion test.
[0024] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0026] Figure 1 This is a metallographic photograph of Example 1 of the present invention;
[0027] Figure 2 This is a metallographic photograph of Comparative Example 1 of the present invention;
[0028] Figure 3 This is a metallographic photograph after corrosion in the GB / T4334 C corrosion test of Example 1 of the present invention;
[0029] Figure 4 This is a metallographic photograph of comparative example 2 of the present invention after corrosion in the GB / T4334 C corrosion test. DETAILED DESCRIPTION
[0030] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0031] C25 steel is a commonly used ultra-pure austenitic stainless steel. Due to its ultra-purified smelting process, the carbon content and other impurities are extremely low, ensuring good corrosion resistance, but sacrificing the strength of the stainless steel.
[0032] In addition, with the traditional forging process, the initial forging temperature is often above 1150°C. At higher forging temperatures, due to the lack of pinning of the precipitated phase at the grain boundary, the grain size of the ultra-pure austenitic steel will rapidly increase, causing a further decrease in strength and affecting corrosion resistance. Cracks and other defects are also prone to occur during the forging process, which also leads to problems such as uneven grains and larger grain sizes of the resulting austenitic stainless steel.
[0033] Therefore, the present invention provides high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel, characterized in that, measured by weight percentage, it includes C≤0.008%, Si≤0.10%, Mn≤0.50%, P≤0.005%, S≤0.005%, Cr: 24.00%~26.00%, Ni: 20.00%~22.00%, Mo≤0.10%, Al≤0.02%, B<0.003%, Zr≤0.6%, Mg≤0.05%, and the balance is Fe.
[0034] Compared with the prior art, the present invention can purify the grain boundaries, inhibit grain growth, make the grains finer and more uniform by adding elements and controlling the content, which helps to improve the strength and toughness of austenitic stainless steel. At the same time, the fine grains can reduce the segregation of impurities at the grain boundaries and improve the corrosion resistance.
[0035] It should be noted that Cr is the main element that plays an anti-corrosion role in the passivation film. In a broad sense, the higher the Cr content, the better the corrosion resistance. However, the increase in Cr content will increase the tendency of ferrite to form in the steel. The intergranular corrosion resistance of ferrite is far inferior to that of austenite. Since Ni has the function of stabilizing austenite, it improves the plastic toughness of steel and is more conducive to deformation during forging. Therefore, more than 20% Ni is required. Combined with the control effect of Zr element on grain growth, smaller grains are obtained. Small grains can better coordinate deformation during deformation, so that a larger deformation amount can be obtained at low temperature. The impurity elements (such as Si, S, P, etc.) at the grain boundaries of austenitic stainless steel are segregated, making the corrosion rate of the grain boundaries higher than that of the grains, which is the main cause of intergranular corrosion. On the one hand, the present invention controls the content of Si, S, P and other elements at a lower level, and on the other hand, by adding zirconium and magnesium elements in combination, the purpose of purifying the grain boundaries and preventing the impurity elements from segregating to the grain boundaries is achieved.
[0036] Since zirconium can inhibit grain growth and make the grains smaller and more uniform, it helps to improve the strength and toughness of austenitic stainless steel. At the same time, fine grains can reduce impurity segregation at the grain boundaries and improve corrosion resistance. Excessive zirconium content will lead to the appearance of some coarse intermetallic compounds formed by zirconium in the steel. These compounds will affect the fluidity and plasticity of the metal during hot working, making the processing more difficult. In addition, too high zirconium content may also change the original phase balance of stainless steel and have an adverse effect on mechanical properties. Its content cannot be higher than 0.6%.
[0037] The role of magnesium is mainly to react with impurity elements such as oxygen and sulfur in austenitic stainless steel, and generate MgO and MgS, reduce the content of impurity elements segregating to grain boundaries, too much magnesium content will first cause an increase in inclusions, reduce the purity of steel, and affect the quality of steel, and secondly, too high magnesium may change the fluidity and viscosity of steel at high temperatures, which is also unfavorable for hot working performance, and finally, abnormal magnesium content may even destroy the passivation film of stainless steel and reduce corrosion resistance. Its content cannot be higher than 0.05%. Under the combined effect of the above two aspects, strength and corrosion resistance can be improved at the same time, so that the tensile strength of the ultra-pure austenitic stainless steel is above 520MPa, the yield strength is above 230MPa, and after corrosion in the GB / T4334 C method corrosion test, there is no phenomenon of intergranular corrosion.
[0038] The present invention also provides a method for manufacturing high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel, comprising the following steps:
[0039] S1: Ingot preparation;
[0040] S2: billet heating;
[0041] S3: multi-fire forging, forging temperature is 800-950℃, final forging temperature is above 600℃, total deformation is 60%~63%;
[0042] S4: Ultra-pure austenitic stainless steel is produced after solution treatment.
[0043] Compared with the prior art, the ultrapure austenitic stainless steel of the present invention adopts a low-temperature large deformation forging method, the forging temperature is controlled at 800-950°C, the total deformation is controlled at 60%-63%, and the forging temperature is much lower than the existing forging temperature (1000-1200°C).
[0044] The forging method using low temperature and large deformation has the following advantages: (1) Improving material properties and refining grains: During the low temperature and large deformation process, severe plastic deformation will occur inside the steel ingot, so that the grains are fully broken and refined. Grain refinement can increase the number of grain boundaries, which can hinder the movement of dislocations, thereby improving the strength and toughness of ultra-pure austenitic stainless steel. (2) Reducing energy consumption: The heating temperature of the forging of the present invention is lower than the existing forging temperature, which means that less energy is consumed during the heating process. Especially for some materials that are sensitive to heating temperature, low temperature forging can avoid the adverse effects of excessively high temperatures on material properties. (3) Improving the processing environment and reducing the generation of oxide scale: Under low temperature conditions, the reaction rate between metal and oxygen is slow, so the oxide scale generated during the forging process is relatively small. The reduction of oxide scale can not only improve the surface quality of the forging, but also reduce the subsequent cleaning workload. It is also beneficial to protect the environment and reduce the health hazards to operators.
[0045] It should be noted that the present invention refines the grain structure by precisely controlling the process parameters and utilizing the work hardening characteristics of the material at low temperatures, while introducing a large number of crystal defects such as dislocations. These defects can become nucleation points for new grains in subsequent processing, thereby achieving the purpose of grain refinement.
[0046] Specifically, in step S3, the forging times are 4-8 times.
[0047] It should be noted that the diffusion capacity of atoms of the austenitic stainless steel provided by the present invention becomes weaker at a lower forging temperature, which will increase the deformation resistance of the material. In order to prevent cracks from occurring during the forging process, the present invention, on the one hand, suppresses grain growth through the mutual cooperation of elements, making the grains finer and more uniform, which helps to improve the strength and toughness of austenitic stainless steel and ensure that no cracks are generated in the subsequent low-temperature large deformation; on the other hand, strictly controls the heating temperature, controls different forging temperatures and deformation amounts according to the different processes of each fire, and avoids the cracking of the forging by cumulative deformation. After 4-8 fires, a larger overall deformation amount is obtained; at the same time, a good organizational foundation is laid for subsequent solution treatment to obtain austenitic stainless steel with better performance.
[0048] Specifically, in step S3, the forging temperature of the first forging is 840°C to 855°C, the final forging temperature is above 600°C, and the deformation amount is 24% to 26%.
[0049] It should be noted that the present invention adopts low-temperature large deformation technology. In order to avoid excessive grain growth, the insulation temperature should not be too high. During the first fire forging, since the steel billet is relatively loose as a whole, the use of a larger deformation forging will not cause the appearance of cracks.
[0050] Specifically, in step S3, the forging temperature of the second fire is 910°C to 925°C, the final forging temperature is above 600°C, and the deformation amount is 19% to 21%.
[0051] It should be noted that after the first fire, the steel billet further transforms into a forged structure. Since there are more dislocations inside after deformation, the deformation resistance increases. If the second fire still uses the same insulation temperature as the first fire, the risk of forging cracks will increase. Therefore, the insulation temperature of the second fire needs to be higher than the insulation temperature of the first fire, which is 910℃~925℃.
[0052] Specifically, in step S3, the forging temperature of the third fire is 790°C to 805°C, the final forging temperature is above 600°C, the spinning center size and the deformation of the center part are controlled to be less than 20.5%.
[0053] It should be noted that the purpose of the third fire is to eliminate center defects. Since the flow degree on the forging surface and the center may be inconsistent, defects will accumulate in the center of the forging. To avoid this situation, the main purpose of the third fire is to increase the deformation in the center of the forging to obtain better overall forging quality and to obtain dimensions consistent with the edges.
[0054] Specifically, in step S3, the forging temperature for the fourth fire and above is 790°C to 805°C, the final forging temperature is above 600°C, and the deformation amount is 12% to 13%.
[0055] It should be noted that the main purpose after the fourth fire is to utilize deformation at a lower temperature to avoid excessive grain growth. As the total deformation increases, the difficulty of deforming forgings at a lower temperature will gradually increase. Therefore, the deformation of the fifth to seventh fires after the fourth fire should not be too large. The deformation of each fire needs to be further reduced to 9% to 12% to ensure that there is no crack while maintaining a certain forging efficiency.
[0056] Specifically, the grain size of the ultra-pure austenitic stainless steel is 6.5, and the grain distribution is relatively uniform.
[0057] Specifically, in step S4, the solution temperature is 950°C-1000°C, and the holding time is 1-2h.
[0058] It should be noted that the present invention adopts an ultra-purified design, and due to the lower C content, the solid solution is carried out at a lower temperature (950°C-1000°C). High-temperature solid solution is mainly to dissolve the carbides precipitated in the steel, and the ultra-purified steel maintains an extremely low C content, so the precipitated carbides are smaller in size and less in number, and are more easily dissolved back into the matrix during solid solution. Therefore, a lower temperature solid solution is adopted, and a lower solid solution temperature controls the growth of the grain size. The fine grains are conducive to the dispersion and distribution of impurity elements during solid solution, and better intergranular corrosion resistance can also be obtained.
[0059] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.
[0060] Example 1
[0061] The preparation method of ultra-pure austenitic stainless steel is as follows:
[0062] S1: Ingot preparation;
[0063] The steel ingot is prepared by ultrapure smelting technology, and its chemical composition is: C: 0.002%, Si: 0.02%, Mn: 0.03%, P: 0.001%, S: 0.001%, Cr: 25.2%, Ni: 22%, Mo: 0.033%, Al: 0.005%, B: 0.0005%, Zr: 0.5%, Mg: 0.05%, and the balance is Fe;
[0064] S2: heating the steel ingot; placing the obtained steel ingot in a heating furnace for heating at a temperature of 850°C;
[0065] S3: Multi-fire forging:
[0066] First fire: the holding temperature is controlled at 850℃, above the final forging temperature of 600℃, the thickness of the forging is pressed from 200mm to 150mm, the deformation is controlled to 50mm, and after the deformation requirement is met, it is returned to the furnace for holding;
[0067] Second fire: The holding temperature is controlled at 920℃, and above the final forging temperature of 600℃, the thickness of the forging is pressed from 150mm to 120mm, and the deformation is controlled to 30mm. After the deformation requirement is met, it is returned to the furnace for holding;
[0068] The third fire:
[0069] The holding temperature is controlled at 800℃. When the final forging temperature is above 600℃, the center size of the forging is spun to 120mm, and the deformation of the center is controlled to 30mm. After the deformation requirement is met, the forging is returned to the furnace for holding.
[0070] Fourth fire: the holding temperature is controlled at 800℃, above the final forging temperature of 600℃, the thickness of the forging is pressed from 120mm to 105mm, the deformation is controlled to 15mm, and after the deformation requirement is met, it is returned to the furnace for holding;
[0071] Fifth fire: The holding temperature is controlled at 800℃, and above the final forging temperature of 600℃, the thickness of the forging is pressed from 105mm to 95mm, and the deformation is controlled to 10mm. After the deformation requirement is met, it is returned to the furnace for holding;
[0072] The sixth fire: the holding temperature is controlled at 800℃, above the final forging temperature of 600℃, the thickness of the forging is pressed from 95mm to 85mm, the deformation is controlled to 10mm, and after the deformation requirement is met, it is returned to the furnace for holding;
[0073] The seventh fire: the holding temperature is controlled at 800℃, above the final forging temperature of 600℃, the thickness of the forging is pressed from 85mm to 75mm, the deformation is controlled to 10mm, and after the deformation requirement is met, it is returned to the furnace for holding;
[0074] The eighth fire: the holding temperature is controlled at 800℃, above 600℃, the finishing size is φ1760*75mm, and it is directly put into water after forging;
[0075] S4: Solution treatment: The forgings are subjected to solution treatment at a temperature of 1000°C and a holding time of 2h to obtain ultra-pure austenitic stainless steel.
[0076] Example 2
[0077] The preparation process of Example 2 is substantially the same as that of Example 1, except that the composition in Example 2 is Zr: 0.3%, Mg: 0.03%, and the balance is Fe.
[0078] Example 3
[0079] The preparation process of Example 3 is substantially the same as that of Example 1, except that in the first firing in Example 3: the holding temperature is controlled at 845°C, the thickness of the forging is pressed from 200mm to 150mm at a temperature above the final forging temperature of 600°C, the deformation is controlled to be 50mm, and after the deformation requirement is met, the forging is returned to the furnace for holding;
[0080] Second fire: The holding temperature is controlled at 915℃, and above the final forging temperature of 600℃, the thickness of the forging is pressed from 150mm to 120mm, and the deformation is controlled to 30mm. After the deformation requirement is met, it is returned to the furnace for holding;
[0081] The third fire:
[0082] The holding temperature is controlled at 800℃, and above the final forging temperature of 595℃, the center size of the forging is spun to 120mm, and the deformation of the center is controlled to 30mm. After the deformation requirement is met, it is returned to the furnace for holding;
[0083] Fourth fire: the holding temperature is controlled at 795℃, above the final forging temperature of 600℃, the thickness of the forging is pressed from 120mm to 105mm, the deformation is controlled to 15mm, and after the deformation requirement is met, it is returned to the furnace for holding;
[0084] Fifth fire: the holding temperature is controlled at 795℃, above the final forging temperature of 600℃, the thickness of the forging is pressed from 105mm to 95mm, the deformation is controlled to 10mm, and after the deformation requirement is met, it is returned to the furnace for holding;
[0085] The sixth fire: the holding temperature is controlled at 795℃, above the final forging temperature of 600℃, the thickness of the forging is pressed from 95mm to 85mm, the deformation is controlled to 10mm, and after the deformation requirement is met, it is returned to the furnace for holding;
[0086] The seventh fire: the holding temperature is controlled at 795℃, above the final forging temperature of 600℃, the thickness of the forging is pressed from 85mm to 75mm, the deformation is controlled to 10mm, and after the deformation requirement is met, it is returned to the furnace for holding;
[0087] The eighth fire: the insulation temperature is controlled at 795℃, above 600℃, the finishing size is φ1760*75mm, and it is directly put into water after forging.
[0088] Example 4
[0089] The preparation process of Example 4 is substantially the same as that of Example 1, except that the solution treatment process in Example 4 is 950°C×2h.
[0090] Example 5
[0091] The preparation process of Example 5 is substantially the same as that of Example 1, except that the components in Example 5 are C: 0.004%, Si: 0.06%, Mn: 0.3%, P: 0.003%, S: 0.003%, Cr: 24.8%, Ni: 21.5%, Mo: 0.08%, Al: 0.02%, B: 0.001%, Zr: 0.3%, Mg: 0.03%, and the balance is Fe.
[0092] Comparative Example 1
[0093] The preparation process of Comparative Example 1 is substantially the same as that of Example 1, except that the components in Comparative Example 1 are C: 0.004%, Si: 0.06%, Mn: 0.3%, P: 0.002%, S: 0.002%, Cr: 25%, Ni: 21.8%, Mo: 0.0330%, Al: 0.005%, B: 0.0005%, and the balance is Fe.
[0094] Comparative Example 2
[0095] The preparation process of Comparative Example 2 is substantially the same as that of Example 1, except that the forging process used in Comparative Example 2 is:
[0096] First fire: heat to 1220℃, keep warm for 35h before forging, and control the deformation to 60%;
[0097] Second fire: holding temperature 1170℃, holding temperature 3h, deformation controlled within 30%;
[0098] The third fire: the holding temperature is 1170℃, the holding time is 3h, and the deformation is controlled at 45%;
[0099] Fourth fire: holding temperature 1140℃, holding temperature 2h, deformation controlled at 55%;
[0100] Fifth fire: insulation temperature 1140℃, insulation for 2h, total deformation controlled at 70%.
[0101] Comparative Example 3
[0102] The preparation process of Comparative Example 3 is substantially the same as that of Example 1, except that the solution treatment process after forging in Comparative Example 3 adopts 1050° C.×2 h and water cooling.
[0103] Performance Testing
[0104] The above examples 1-5 and comparative examples 1-3 were tested for performance, including tensile strength Rm, yield strength R p0.2 The test results are shown in Table 1; after the embodiments 1, 4 and comparative examples 2 and 3 were subjected to the GB / T4334 C method corrosion test, the corrosion rates are shown in Table 2.
[0105] Table 1 Performance test results
[0106] Group Rm / MPa <![CDATA[R p0.2 / MPa]]> A / % Z / % Example 1 538 231 51.5 80 Example 2 522 237 46 81 Example 3 530 233 50 80 Example 4 548 238 48 79 Example 5 536 233 49 80 Comparative Example 1 509 220 45 78 Comparative Example 2 468 164 61 85 Comparative Example 3 490 208 50 82
[0107] Table 2 Corrosion rate
[0108]
[0109]
[0110] It can be seen from the combination of Examples 1-5 and Comparative Examples 1-3 and referring to Table 1 that the ultra-pure austenitic stainless steel obtained in Examples 1-5 of the present invention has high strength and corrosion resistance, and the ultra-pure austenitic stainless steel has a tensile strength of more than 520 MPa, a yield strength of more than 230 MPa, an elongation after fracture A of more than 46%, and a cross-sectional shrinkage Z of more than 79%.
[0111] Combining Examples 1 and 4 with Comparative Example 3 and referring to Table 2, it can be seen that the corrosion rates of the lower temperature solid solution adopted by the present invention are almost the same as those of the conventional 1050°C solid solution, and the lower temperature solid solution can also obtain a lower corrosion rate.
[0112] Reference Figure 1-4 In combination with the embodiments and comparative examples, it can be seen that the process of the present invention can effectively reduce the grain size. The grains of forgings forged by conventional methods are relatively coarse, with an average grain size of 2.5 and accompanied by a certain mixed crystal phenomenon, while the grain size of the forgings in the present invention can reach 6.5, and the grain distribution is relatively uniform.
[0113] After corrosion according to the C method corrosion test of GB / T4334-2020, the intergranular corrosion depth of the forgings of Example 1 and Comparative Example 2 is compared as follows Figure 3 and 4 As shown, after the C-method corrosion test, the forgings forged by conventional methods can be clearly observed to have intergranular corrosion at the cross section, while after the corrosion test of the forgings manufactured by the present invention, no obvious corrosion phenomenon is observed at the grain boundaries.
[0114] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel, characterized in that: Calculated by weight percentage, it includes C≤0.008%, Si≤0.10%, Mn≤0.50%, P≤0.005%, S≤0.005%, Cr: 24.00%~26.00%, Ni: 20.00%~22.00%, Mo≤0.10%, Al≤0.02%, B<0.003%, Zr≤0.6%, Mg≤0.05%, and the balance is Fe.
2. The high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel according to claim 1, characterized in that: According to weight percentage, it includes C: 0.002-0.004%, Si≤0.060%, Mn≤0.30%, P≤0.003%, S≤0.003%, Cr: 24.80%-25.20%, Ni: 21.50%-22%, Mo≤0.80%, Al≤0.15%, B<0.002%, Zr: 0.3%-0.5%, Mg: 0.03%~0.05%, the balance is Fe.
3. The high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel according to claim 1 or 2, characterized in that: The ultra-pure austenitic stainless steel has a grain size of 6.5 and a relatively uniform grain distribution.
4. The high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel according to claim 1 or 2, characterized in that: The ultra-pure austenitic stainless steel has a tensile strength of more than 520 MPa and a yield strength of more than 230 MPa.
5. A method for manufacturing high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Ingot preparation; S2: Ingot heating; S3: multi-fire forging, forging temperature is 800-950℃, final forging temperature is above 600℃, total deformation is 60%~63%; S4: Ultra-pure austenitic stainless steel is produced after solution treatment.
6. The method for manufacturing high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel according to claim 5, characterized in that: In step S3, the forging times are 4-8 times.
7. The method for manufacturing high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel according to claim 5, characterized in that: In step S3, the forging temperature of the first forging is 840°C to 855°C, the final forging temperature is above 600°C, and the deformation amount is 24% to 26%.
8. The method for manufacturing high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel according to claim 5, characterized in that: In step S3, the forging temperature of the second fire is 900°C to 925°C, the final forging temperature is above 600°C, and the deformation amount is 19% to 20.5%.
9. The method for manufacturing high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel according to claim 5, characterized in that: In step S3, the forging temperature of the third fire is 790°C to 805°C, the final forging temperature is above 600°C, and the deformation of the central part is controlled to be 19% to 20.5%.
10. The method for manufacturing high-strength and high-corrosion-resistant ultra-pure austenitic stainless steel according to claim 5, characterized in that: In step S4, the solution temperature is 950°C-1000°C, and the holding time is 1-2h.